Temporal Bone Trauma: To Pull Down the Wall of Incommunicableness - Assunta Scuotto; Michele Rotondo (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
In the past decades, treatment of the temporal bone traumas (TBTs) was undeniably improved by advances in neuroradiological and in neuro-oto-surgical fields. However, these advances did not systematically enhance the quality of the approach to TBTs. Maybe they did not systematically target towards treatment- guidelines standardization. We suggest a simplified approach to TBTs, trying to enhance the communication among the different specialists involved in the matter, above all between the radiologists and not-radiologists.